Analysis of Accelerated Weathering and Mechanical Properties of HDPE Polymer Composites with Carbon Black and Zinc Oxide Nanoparticles for Floating Solar Power Plants - Mohammed khan; Rai Sujit Nath Sahai (Journal of Renewable Energy and Environment)
The research aimed to create a composite material for the floaters used in floating solar power plants. High-density polyethylene (HDPE) was combined with 1, 1.5, 2, and 2.5% of carbon black (CB) and 1,2,and 3% of zinc oxide (ZnO). Mechanical tests were carried out after accelerated weathering for 311, 634, 954, 1403, and 2878 hours in dry (out of water) and wet (sample floating in water) conditions. HDPE loses tensile strength, impact resistance, and elongation at break after 634 hours and 954 hours of weathering. The Shore D hardness did not show any significant change. The best performance was observed in batches D4 and W4, which contain 2% CB and 1% ZnO, in dry and wet conditions. The SEM (scanning electron microscope) shows the external morphology of D1 and W1 (pure HDPE) and D4 and W4 (composite) and revealed that pure HDPE was more degraded compared to the composite. Thermal properties and stability were analyzed using TGA (Thermogravimetric analysis). A further increase in CB and ZnO will reduce the strength of the composite.It was found that HDPE with 2% CB and 1% ZnO was a good composite material for developing the floaters used in floating solar power plants.